Sosialisasi Pemanfaatan Akal Imitasi (AI) dalam Dunia Pendidikan di SMKN 4 Kota Bekasi - Zetty Karyati; Rahmawati Rahmawati; Anggun Citra Dini Dwi Puspitasari; Muhamad Khairul Anwar (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
The development of digital technology is transforming various aspects of life, including education, with Artificial Intelligence (AI) emerging as a significant innovation that has a profound impact. Socialization activities on the use of Artificial Intelligence (AI) at SMKN 4 Kota Bekasi aim to enhance technology literacy among students and educators. These activities aim to enhance the understanding and awareness of students and educators at SMKN 4 Kota Bekasi regarding the basic concepts of AI, its benefits and risks, as well as how to integrate it wisely into the learning process. The activities also aim to build awareness of the importance of adapting to technology and to encourage innovation in the field of education. The methods used in the socialization activities include material presentations, interactive discussions, and demonstrations of AI applications in education. The results of the activities show an increase in participants' understanding of the potential and challenges of AI, as well as readiness to utilize AI in the learning process. This socialization serves as an initial step in building an educational environment that is adaptive to technological developments and capable of producing a competent generation in the digital era.